ҲӘЗИРГИ ПОВЕСТЬЛЕРДЕ МИЛЛИЙЛИГИМИЗ ТЫМСАЛЫ МУҲАДДЕС ИНСАНЛАР КЕЛБЕТИ (Ш.Уснатдинов повестьлери мысалында) - Алламбергенов, К.; Сагидуллаева, З.Б. (FAN va JAMIYAT, 2019)
The object of the article is the stories «Whom it’s late, whom it’s a dawn», «The last hunter» by the famous writer-publicisth Sh.Usnatdinov. There have been analyzed haw the writer entered the Karakalpak prose through the artistic publicistic school, the author’s individual ways of deseription, artistic search and shill in the creation of heroes’ images.